Effectiveness Of Isometric Handgrip Excercise In Controlled Blood Pressure In Hypertension Patients: A Systematic Review and Meta-Analysis - Trisno Putri, Noor Rochmah Ida Ayu; Astuti, Verra Widhi; Hamidah, Sofiatul; Ridiana, Marsela (Universitas Harapan Bangsa, 2025)
Hypertension is a major factor in cardiovascular disease, causing high morbidity and mortality. Several pharmacological therapies are available, but many patients do not achieve optimal blood pressure control. Isometric handgrip exercise is one of the non-pharmacological intervention that is inexpensive, practical and efficient. The research method use a literature search conducted in the PubMed, Cochrane, and Web of Science databases until May 2025. Article included were randomized controlled clinical trials (RCTs), cross-sectional trials, and quasi-experimental studies that examined the effect of isometric handgrip on blood pressure in patients with pre-hypertension or hypertension. The primary outcomes were systolic blood pressure, diastolic blood pressure and mean arterial pressure (MAP). The research result showed that isometric handgrip exercise can reduce systolic blood pressure by an average of 7.3 to 7.5 mmHg and diastolic blood pressure by 3.2 to 3.9 mmHg, and MAP by 5.9 to 7.2 mmHg, with tan effect equivalent to that of antihypertensive drugs. Exercise with an intensity of 30 o 60 MVP or 85 to 95% HRpeak performed to 3 to 5 times per week has been shown to be most effective. Isometric handgrip also reduce hypertension symptoms such as dizzies and fatigue, and no serious side effect were found. It can be concluded that isometric handgrip exercise can be used as a safe and effective complementary therapy for hypertension management and is worth considering as part of a lifestyle change for hypertension patients.